Filsafat Hidup di Bokong Truk Dalam Terminologi Logoterapi Spiritual - Hidayat, Muhtar Sofwan; Sugiyanto, Bambang; Syam, Robingun Suyud El (STAI Denpasar Bali, 2023)
This research seeks to investigate the philosophy of life on the back of a truck in terms of spiritual logotherapy, where previous research has not focused on this aspect. The research is qualitative with descriptive design and analysis. The results of the research show that the writing on the buttocks of trucks is a reality of life in Indonesian society. Through a spiritual logotherapy approach, these writings provide spiritual encouragement to live life as it is, because understanding reality will lead to happiness. This study has theoretical implications, namely exploring the background of the writing on the truck's rear in detail, then synthesizing it into a life lesson so that the positive side can be used as a lesson to emulate, and the negative side can be avoided. The practical implication is that this research can be used as a reference for lovers of texts on the backs of trucks to provide education for the public, regarding the positives and negatives. The research provides recommendations for academics who wish to investigate the philosophy of life in the back of a truck, as well as the need for a broader understanding of its essence